Evaluation of human papillomavirus DNA in colorectal cancer and adjacent mucosal tissue samples - Galati, Luisa; Gupta, Purnima; Tufaro, Antonio; Marinaro, Mariarosaria; Saponaro, Concetta; Escobar Marcillo, David Israel; Loisi, Donato; Sen, Rajdip; Robitaille, Alexis; Brancaccio, Rosario N; Cuenin, Cyrille; McKay-Chopin, Sandrine; et al. (Infectious agents and cancer, 2023)
BACKGROUND: Although the role of viral agents, such as human papillomavirus (e.g. HPV16, HPV18) in colorectal cancer (CRC) has been previously investigated, results remain inconclusive. METHODS: To further evaluate the involvement of oncogenic HPV types in CRC, 40 frozen neoplastic and 40 adjacent colonic tissues collected from Italian patients were analyzed by Luminex-based assays that detect a broad spectrum of HPV types, i.e. Alpha (n = 21), Beta (n = 46) and Gamma HPVs (n = 52). In addition, 125 frozen CRC samples and 70 surrounding mucosal tissues were collected from Czech patients and analyzed by broad spectrum PCR protocols: (i) FAP59/64, (ii) FAPM1 and (iii) CUT combined with Next Generation Sequencing (NGS). RESULTS: Using Luminex-basedassays, DNA from HPV16 was detected in 5% (2/40) CRC tissues from Italian patients. One HPV16 DNA-positive CRC case was subsequently confirmed positive for E6*I mRNA. Cutaneous beta HPV types were detected in 10% (4/40) adjacent tissues only, namely HPV111 (n = 3) and HPV120 (n = 1), while gamma HPV168 (n = 1) and HPV199 (n = 1) types were detected in adjacent and in tumor tissues, respectively. The NGS analysis of the CRC Czech samples identified HPV sequences from mucosal alpha-3 (HPV89), alpha-7 (HPV18, 39, 68 and 70) and alpha-10 species (HPV11), as well as cutaneous beta-1 (HPV20, 24, 93, 98, 105,124) beta-2 (HPV23), beta-3 (HPV49) and gamma-1 species (HPV205). CONCLUSIONS: Our findings indicate that HPV types belonging to the mucosal alpha, and the 'cutaneous' beta and gamma genera can be detected in the colonic mucosal samples with a low prevalence rate and a low number of HPV reads by Luminex and NGS, respectively. However, additional studies are required to corroborate these findings.